Differential morphology of the hemocytes present in pupal ovaries of the queen and worker honeybee - Da Cruz-Landim, Carminda [UNESP] (International Society of Cytology, 2001)
The location and morphological features of the blood cells found in the pupal ovary of workers and queens of Apis mellifera are described in relationship with their probable function in the ovary differentiation. The hemocytes from inside the ovarioles are different in both castes. In queens their morphology suggest an action in the tunica propria production, while in workers it suggest a phagocytic activity. The hemocytes present in the intersticial tissue are phagocytes in both castes, and may be responsible by the ovary shapping during metamorphosis.
Keywords: Castes; Differentiation; Hemocytes; Ovary; Queen; Tunica propria; Worker